Methoxyacetic acid (MAA) causes digit malformations of mice when it was given orally on gestation day 11. Previous observation showed that malformation was caused by cell death. The aims of the research were to determine the types of cell death, first time of cell death and their distribution pattern on forelimb bud of Swiss Webster (SW) mice. Ten mM/kg of body weight (bw) of MAA were administered by gavage to SW mice on gestation day 11. Forelimb bud of mouse embryos of gestation day 11 + 0, 1, - AGUS HARYONO; TIEN WIATI SURJONO; LIEN ALINA SUTASURYA; SRI SUDARWATI (Bogor Agricultural University, Indonesia, 2011)
Methoxyacetic acid (MAA) causes digit malformations of mice when it was given orally on gestation day 11. Previous observation showed that malformation was caused by cell death. The aims of the research were to determine the types of cell death, first time of cell death and their distribution pattern on forelimb bud of Swiss Webster (SW) mice. Ten mM/kg of body weight (bw) of MAA were administered by gavage to SW mice on gestation day 11. Forelimb bud of mouse embryos of gestation day 11 + 0, 1, 2, 3, 4, 5 hours were processed with paraffin method and were made plantar section. Cell death at plantar section were colored with 4,6-diamino-2-phenylindole hydrochloride (DAPI) and hematoxylin. The result showed, that digit malformations initially by apoptosis mesenchymal cell at proximal of axial mesoderm in around of primary axial artery has done one hour after treatment. Apoptosis at the axial area, the site formation of digital ray III distributed to preaxial area where digits I and II are formed, and to the site formation of digits IV and V. The number of mesenchyme cell of digital rays II, III, and V was decrease by the increasing of gestation day, while digital ray was not formed and finally digits I, II, III, and V were missing. The reduction number of cell of digital ray IV were delayed time to be formed and its small size. Thereby it can be concluded, that MAA induced digit malformations of SW mice started by apoptosis which is occurrence has been increase in area of digital ray formation, so that digital ray can not be formed, but when formed it will not developed.